Chlamydial infection as a possible aetiological factor in the Guillain-Barré syndrome. Issue 686 (December 1982) - Grattan, C. E. H.; Berman, P.
Abstract : Two cases of Guillain-Barré syndrome are reported with serological evidence of recent Chlamydia psittaci infection. It is suggested that the chlamydial infection may have precipitated the neurological syndrome.